2011
DOI: 10.1002/hipo.20802
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neurogenesis by targeted hippocampal irradiation fails to affect kindling progression

Abstract: Changes in the rate of dentate granule cell neurogenesis and in the fate of newborn granule cells have been implicated in the development and progression of epilepsies. Strategies to normalize neurogenesis in chronic epilepsy models are thought to increase our understanding of the functional consequences of aberrant neurogenesis in the epileptic brain. Therefore, we modulated neurogenesis in an amygdala kindling paradigm in rats by targeted irradiation of the hippocampus using a medical linear accelerator devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
(63 reference statements)
5
29
1
Order By: Relevance
“…Surprisingly, in the present study, proliferation and generation of newborn neurons were induced by repeated seizures regardless of the genetic modulation of the endocannabinoid system. It has also been shown that the kindling process itself leads to increased hippocampal neurogenesis (Aguado et al, 2005;Jafari et al, 2012b;Parent et al, 1998;Pekcec et al, 2010), here pointing toward kindling associated alterations of cell proliferation. These data suggest that the endocannabinoid system plays no role in the disease-associated modulation of neurogenesis in the kindling model of temporal lobe epilepsy.…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 83%
“…Surprisingly, in the present study, proliferation and generation of newborn neurons were induced by repeated seizures regardless of the genetic modulation of the endocannabinoid system. It has also been shown that the kindling process itself leads to increased hippocampal neurogenesis (Aguado et al, 2005;Jafari et al, 2012b;Parent et al, 1998;Pekcec et al, 2010), here pointing toward kindling associated alterations of cell proliferation. These data suggest that the endocannabinoid system plays no role in the disease-associated modulation of neurogenesis in the kindling model of temporal lobe epilepsy.…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 83%
“…However, studies on whether aberrant hippocampal neurogenesis contribute to epileptogenesis have produced mixed results. Some studies using pharmacological agents (Jung et al, 2004(Jung et al, , 2006Sugaya et al, 2010) or genetic approaches (Cho et al, 2015;Hosford et al, 2016) concluded that inhibiting the newborn granule cells leaded to reduced spontaneous recurrent seizures (SRSs), while others indicated that ablation of newborn granule cells via pharmacological agents (Radley and Jacobs, 2003;Pekcec et al, 2008) or selective hippocampal irradiation (Pekcec et al, 2011) did not alleviate chronic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Papers by Jung et al (2006), Sugaya et al (2010) and Pekcec et al (2007) demonstrated a reduction in HECs after ablation of hippocampal neurogenesis, but MSF was not measured. In another study (Pekcec et al, 2011), neither the HECs nor the MFS was examined. In particular, the generation of hilar basal dendrites, another common pathological integration, was poorly assessed in these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed results were obtained from studies aimed at preventing epileptogenesis by experimental reduction of neurogenesis (7,8). The complexity of the influence of newly added cells to existing circuitry was also demonstrated in early neural transplantation studies, in which new neurons transplanted into the hippocampal formation exerted either proconvulsive or anticonvulsive effects depending on the cell source used (9).…”
mentioning
confidence: 99%